1987
DOI: 10.1111/j.1365-2125.1987.tb03195.x
|View full text |Cite
|
Sign up to set email alerts
|

Early cardiovascular changes with ibopamine: evidence for a biphasic haemodynamic action.

Abstract: 1 The haemodynamic effects of ibopamine, an oral dopamine derivative, were studied in eight patients with left ventricular dysfunction using invasive catheterisation techniques. 2 An early rise was seen in the mean right atrial pressure (P < 0.05), the mean capillary wedge pressure (P < 0.01) and the mean pulmonary arterial pressure (P < 0.001) which occurred at 15 min and persisted for 30 min.3 A second, later, positive chronotropic effect was seen as an increase in the heart rate (P < 0.05) at 45 min with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Indeed, cardiac output may rise already = 0.5 h after a single oral dose of = 200 mg IBO, and this increase may be maintained for ~ 4 h, while, in some studies, systemic vascular resistance fell only -~ 1-2 h after administration following a transient rise in arterial pressure [4][5][6][7][8][9][10][11][12][13][14][15][16]. Hence, the early and transient rise in thoracic blood volume may have been caused by cardiac enlargement in response to a temporary increase in systolic blood pressure and, thus, left ventricular afterload in the absence of an effect on peripheral veins and in spite of the positive inotropic effect of the dose (200 mg) of IBO used [4][5][6][7][8][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, cardiac output may rise already = 0.5 h after a single oral dose of = 200 mg IBO, and this increase may be maintained for ~ 4 h, while, in some studies, systemic vascular resistance fell only -~ 1-2 h after administration following a transient rise in arterial pressure [4][5][6][7][8][9][10][11][12][13][14][15][16]. Hence, the early and transient rise in thoracic blood volume may have been caused by cardiac enlargement in response to a temporary increase in systolic blood pressure and, thus, left ventricular afterload in the absence of an effect on peripheral veins and in spite of the positive inotropic effect of the dose (200 mg) of IBO used [4][5][6][7][8][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it cannot be excluded that our study period was too brief to document a small, late effect of IBO on capacitance veins. Indeed, ventricular filling pressures may show a biphasic response after a single oral dose of = 200 mg IBO, with an early rise, ~ 0.5-1 h after administration, and a late fall, starting = 2 h after administration [4][5][6][7][8][9][10][11][12][13][14], and this could be associated with a fall and rise in venous capacitance. This may explain why IBO resulted in a fall rather than a rise in left ventricular and thoracic blood volume in patients given ISMN, at 120 min, in agreement with a study where echocardiography showed a fall in cardiac dimensions --2 h after 200 mg IBO [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A transient increase in ar terial blood pressure and pulmonary capil lary wedge pressure has been reported. The effect is secondary to a-mediated vasocon striction [37], especially when larger doses of ibopamine are used.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%